Towards molecular autopsies: Internal validation of the Qubit 1 X dsDNA HS Assay Kit - Naidoo, Adele (Department of Pathology, 2025)
Molecular autopsies are post-mortem genetic analyses that can be used to aid in cause of death determination, especially in sudden unexpected death cases. Molecular autopsies involve analysing the decedent's DNA to identify potential pathogenic genetic variants. Accurate quantification of the DNA and associated sequencing libraries is essential, however, no validation studies have been published on the recommended fluorometric quantification methods. The aim of this study was to internally validate the Qubit™ 1X dsDNA HS Assay Kit on the Qubit™ 4 Fluorometer as part of a molecular autopsy workflow for forensic applications. The Qubit™ 1X dsDNA HS Assay workflow was optimised and then used to assess the DNA concentration of control Lambda DNA, extracted DNA from forensic samples and DNA sequencing libraries. The accuracy, precision, dynamic range, and sensitivity were established in accordance with ISO 17025 standards. All parameters met the manufacturer's criteria of acceptance except for the precision of measurements for samples with DNA concentrations ≥ 0.5 ng/µl which were expected to be < 1% CV. The precision of the measurements (1.54% CV – 2.47 % CV), however, was deemed acceptable for our laboratory, as downstream DNA sequencing results surpassed quality thresholds. Additionally, DNA concentration measurements obtained from this DNA quantification workflow were similar to those obtained from other methods that have previously been validated in our laboratory. Overall, the Qubit™ 1X dsDNA HS Assay Kit was considered internally validated for DNA quantification in our laboratory and deemed fit for purpose. This study has enabled the use of this assay in the forensic setting for the first time and has advanced our progression towards implementing a molecular autopsy sequencing workflow in South Africa